Alveolar socket healing in 5-lipoxygenase knockout aged female mice treated or not with high dose of zoledronic acid - Ramez H. Mahmoud (Nature Portfolio, 2021)
Abstract This study investigated the role 5-lypoxigenase (5-LO) on alveolar socket healing in aged female mice treated with zoledronic acid (ZL). Forty 129/Sv female mice (64–68 weeks old), 20 wild type (WT) and 20 5-LO knockout (5LOKO) were equally distributed according to ZL treatment: WT Control, WT ZL, 5LOKO Control, and 5LOKO ZL. ZL groups were treated with an intraperitoneal injection of 250 µg/Kg of ZL, while controls were treated with saline. Treatments were administered once a week, starting four weeks before surgery for tooth extraction and until 7 and 21 days post-surgery. Mice were euthanized for a comprehensive microscopic analysis (microCT, histomorphometry and immunohistochemistry). WT ZL mice presented intense inflammatory infiltrate (7 days), delayed bone formation (21 days), reduced collagenous matrix quality, and a deficiency in Runx-2 + , TRAP + , and macrophages as compared to controls. 5LOKO ZL animals presented decreased number of Runx-2 + cells in comparison to 5LOKO Control at 7 days, but no major changes in bone healing as compared to WT or 5LOKO mice at 21 days. The knockout of 5LO favored intramembranous bone healing in aged female mice, with a direct impact on inflammatory response and bone metabolism on the development of ONJ-like lesions.